Tranformasi Manajemen Universitas menggunakan Framework Cobit 5 di Era Industri 4.0 - Seri Hartati; Amir Syamsuadi; Luluk Elvitaria (Jayapangus Press, 2020)
The Industrial Revolution 4.0 has brought the consequences of increasing demands for accountability, transparency for all organization. This is made about a change in the organizational design paradigm. In this RI 4.0, adactive power and fast responsive are the key to success achieving the organization's vision and mission. . It is a challenge for universities to adjust various problems in this era of disruption. The transformation of educational organizations is one of alternative in order to realize that is oriented to public services and to prepare competent human resources in their fields. This research offers a solution for universities to find out how far the university is prepared to face this era. The research used a descriptive method with a qualitative approach. By using purposive sampling and determined data source by snowball, the results showed that the transformation of universities in Riau had to immediately adapt of demands in RI 4.0. The IT management level process showed that it was still in level 2, which is the managed process level. These processes were still at level 1 and level 2 so they need to be increased to a minimum at level 3 (Established). It is recommended to improve the management of IT services and the application of information security management become more effective, increasing the adaptive power of the industrial revolution 4.0